Daytime sleepiness in Chinese professional, semi professional and students soccer players in the Shanghai lockdown - Songhui You; Antonio Cicchella (BMC, 2023)
Abstract Purpose April-May 2021 Shanghai city was under strict lockdown. Soccer players suffered from the restrictions, being unable to train and have a social life. The aim of this study was to compare differences in daytime sleepiness between genders and qualification levels in a cohort university Chinese soccer player under 0 Covid policy restrictions in the urban area of Shanghai. Methods 491 questionnaires of Epworth Sleepiness Scales (ESS) were compiled online by male and female Soccer Students (SS), Semi-Professional players (SP) and Professional Players (PP) during the ongoing restriction measures post Shanghai lockdown. ANOVA was performed for players levels and gender. Results Significant differences were found between the 3 levels and between males and females. PP showed a very low score in the ESS (5,97) well below the threshold of 8 for daytime sleepiness, while SS and SP showed an ESS score above the threshold. Female showed higher scores in comparison to males. Differences between males and females reflect the confinement conditions in the ESS items, showing more difference in the item of ESS which are related with indoor situations. Conclusions This study shows the first data on sleepiness in Chinese soccer players of different level of qualification immediately post lockdown condition. Professional male's players sleepiness was lower, than females, SS and SP after the exceptional lockdown measures. The reasons can reside in the more ordered lifestyle of PP in comparison to SS and SP, which mitigated the effects of the lockdown. Our results suggest that measures to improve sleep in females' soccer player should be adopted if these exceptional conditions will happen again.